Analisis SWOT Pembelajaran Daring Mahasiswa Kebidanan Pada Masa Pandemi Covid-19 - Sukma Adnyani, Ni Wayan; Krisda Elvina, Velintina (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
The purpose of this study was to analyze the effectiveness of online learning with a SWOT matrix analysis for DiplomaIII midwifery students during the Covid-19 pandemic at the Polytechnicof Health Kartini Bali. The method in this research is qualitative, with analysis using the SWOT matrix approach to formulate strategies to improve the quality of online learning for students. The research subjects were 15 representatives of Level I, II and III students. Collecting data using a questionnaire with a closed list of questions containing internal and external variables that affect learning. The results showed that from the results of the SWOT analysis, four alternative strategies were formulated, namely the Strategy Strength-Opportunities (SO), Weaknesses-Opportunities (WO), Strength-Threats (ST), and Weaknesses-Threat (WT) which included quality improvement in terms of methods. learning (providing modules, elerning and video tutoral), infrastructure (internet quota), human resources (participant motivation) and related stakeholder commitment. So it can be concluded that SWOT analysis on online learning can be used as input in improving the quality of learning for organizers, students and institutions in supporting the success of online learning during the Covid-19 period at the Polytechnicof Health Kartini Bali.